D Uptake of ultrasmall superparamagnetic particles of iron oxide predicts growth in abdominal aortic aneurysms: a Pilot Study. (9th June 2011) - Richards, J M J; Semple, S I; Gillivray, T J Mac; Gray, C; Langrish, J P; Williams, M; Dweck, M; Wallace, W; McKillop, G; Chalmers, R T A; Garden, O J; Newby, D E
Abstract : Background: Prediction of abdominal aortic aneurysm (AAA) expansion and rupture is challenging and currently relies on serial measurements of maximum aneurysm diameter. Using ultrasmall superparamagnetic particles of iron oxide (USPIO) and MRI, we aimed to assess whether areas of cellular inflammation correlated with the rate of abdominal aortic aneurysm expansion. Methods and Results: An image acquisition and data analysis algorithm for the detection of focal USPIO accumulation in tissues was developed. Patients (n=29; 27 male; aged 70±5 years) with asymptomatic AAA (4.0–6.6 cm) were recruited from an outpatient surveillance programme and underwent 3T MRI before and 24–36 h after administration of USPIO. The change in T2* value on T2*-weighted imaging was used to detect accumulation of USPIO within the abdominal aortic aneurysm. Histology of aortic wall tissue samples confirmed co-localisation and uptake of USPIO in areas with macrophage infiltration. Patients were classified into one of three groups on the basis of imaging findings (Abstract D Figure 1 ). Group 1: periluminal USPIO uptake only. Group 2: USPIO uptake throughout the thrombus. Group 3: USPIO uptake in the aortic wall. Patients in group 3 with distinct mural uptake of USPIO had a threefold higher growth rate (n=13; 0.66 cm/yr; p=0.020) than those with no (Group 1; n=7; 0.22 cm/yr) or non-specific USPIO uptake (Group 2; n=9; 0.24 cm/yr) despite having similar aneurysm diameters (5.4±0.6, 5.1±0.5 and 5.0±0.5 cm respectively; p>0.05) and patient characteristics (p>0.05). In one patient with an inflammatory aneurysm, USPIO uptake and inflammation extended beyond the aortic wall into surrounding tissues. Conclusion: USPIO uptake in the aortic wall detects cellular inflammation in patients with AAA and appears to predict more rapidly progressive AAA expansion. This technique therefore holds major promise as a new method of risk-stratifying patients with AAA that extends beyond the simple anatomical measure of aneurysm diameter.